Democracy and climate change - Hanusch, Frederic (Routledge, Taylor & Francis Group, 2018)
chapter 1 Introduction -- part I The basis for the analyses -- chapter 2 The unknown infl uence of democratic qualities on climate performance -- chapter 3 The concept and the operationalization of democratic effi cacy -- part II An empirical analysis of the democracy-climate nexus -- chapter 4 Analysis I: more leads to more – positive statistical trends -- chapter 5 –2012 – a case study perspective -- chapter 6 1995–1997: Chrétien makes use of the prerogative -- chapter 7 1998–2002: futile consultations National activities in the form of a National -- chapter 8 2003–2005: undemocratic unpredictability -- chapter 9 2006–2012: democratic weakening and climate change as a shield issue -- chapter 10 Discussion analysis II: linkages between democratic quality and climate performance -- part III Synergy -- chapter 11 Overall discussion -- chapter 12 Conclusion -- chapter Pragmatic afterword -- part Appendices -- chapter A Stata do file -- chapter ? Expert interview guidelines -- chapter C Interview partners.
Keywords: Erde; Electronic books; Internationaler Vergleich; Demokratie; Klimaschutz; Umweltpolitik; Klimaänderung